ANALISIS KEBIJAKAN PENDIRIAN SEKOLAH DASAR DI KABUPATEN BATU BARA - Regina Sipayung; Din Oloan Sihotang; Johannes Sohirimon Lumban Batu (Universitas Negeri Medan, 2021)
This study uses a descriptive methodology with interview data collection techniques, observation and documentation studies. The results showed that of the 17 schools that were established and categorized since 2018 it was found that 37% of the schools did not meet the study group requirements because there were less than 20 students. Then, judging from the communication process, the socialization of the requirements for the establishment of schools has not been carried out properly, information regarding the determination of school conditions is only conveyed to the school establishment committee. The readiness of resources has not been met and the disposition process still needs attention. The bureaucratic structure factor is still not clear, the standard operational procedures of the Batu Bara District Education Office have been guided by Kepmendiknas No. 060/U/2002. Based on the conclusion of this study, it was found that the Education Office of Batu Bara Regency had implemented policies in accordance with the Ministry of National Education. Number 060/U/2002, but needs to do some repairs.Keywords: Policy, School Establishment, Edwards